THE INFLUENCE OF COMPENSATION, TRAINING, COMPETENCE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE PT. LUAS RETAIL INDONESIA - Maizar; Indra Nara Persada; Septa Diana Nabella (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This study supposed to determine the effect of compensation, training, competence and work discipline on employee performance of pt luas retail indonesia in batam branch. the sampling technique in this study is a census, the entire population makes a sample of 93 people. research instruments interviews and questionnaires. data analysis using multiple regression tests, t tests, and f tests with spss version 25. the research results are as follows: compensation has a positive and significant effect on employee performance of pt luas retail indonesia with a t value of 9.567>1.661 t table and a significance of 0.000 <0.05. training has a positive and significant effect on employee performance of pt. luas retail indonesia with a t value of 6.370>1.661 t table and a significance of 0.000 <0.05. competence has a positive and significant effect on employee performance of pt. luas retail indonesia with a t value of 5.723>1.661 t table and a significance of 0.000 <0.05. work discipline has a positive and significant effect on employee performance of pt. luas retail indonesia with a t value of 5.992>1.661 t table and a significance of 0.000 <0.05. compensation, training, competence and work discipline simultaneously have a positive and significant effect on employee performance of pt. luas retail indonesia with the value of f count 150.761>2.70 f table and significance 0.000<0.05.